The Effect of the Use of Information Technology (Tapping Box) and Taxpayer Awareness on Taxpayer Compliance in Paying Restaurant Tax in Sumedang Regency - Nitha Dwi Afianti; Fanji Farman; Fahrul Alam Masruri (LPPM Universitas Sebelas April, 2020)
The core of the research problem is the not yet optimal use of information technology (Tapping Box) and taxpayer awareness of taxpayer compliance in paying restaurant taxes. This research aims to determine the effect of the use of information technology (Tapping Box) and taxpayer awareness on taxpayer compliance in paying restaurant taxes in Sumedang Regency. The method used is quantitative research with a survey approach. The sample used the saturated sampling method which was carried out on 59 restaurant taxpayer respondents who had been installed with the Tapping Box. The data used are primary data collected through the distribution of questionnaires. The data analysis technique used is MSI, simple regression analysis, multiple regression analysis, correlation coefficient, coefficient of determination, t test, and F test. The results show that partially the use of information technology (Tapping Box) has a positive effect on taxpayer compliance resulting in tcount 3,271 > ttable 2,003 and taxpayer awareness has a positive effect on taxpayer compliance resulting in tcount 3,756 > ttable 2,003. Simultaneously, the use of information technology (Tapping Box) and taxpayer awareness has a positive effect on taxpayer compliance resulting in Fcount 8,631 > Ftable 3,16. The use of information technology (Tapping Box) and taxpayer awareness has an effect on taxpayer compliance by 23,6%.